Epicardial adipose tissue: the genetics behind an emerging cardiovascular marker. (25th November 2020) - Sousa, J.A; Serrao, M.G; Temtem, M; Pereira, A; Santos, M; Mendonca, F.V; Monteiro, J.P; Ferreira, A; Freitas, P; Henriques, E; Ornelas, I; Freitas, A.I; et al.
Abstract: Background: Increasing evidence points epicardial adipose tissue (EAT) as an emerging cardiovascular risk marker. Whether genetic polymorphisms are associated with a higher EAT burden is still unknow. Genetic risk score (GRS) is an emerging method that attempts to establish correlation between single nucleotide polymorphisms (SNPs) and clinical phenotypes. Aim: Evaluate the role of genetic burden and its association to EAT. Methods: 996 patients (mean age 59±8, 78% male) were prospectively enrolled in a single center. EAT was measured on cardiac CT using a modified simplified method. Patients were divided into 2 groups (above vs. below the median EAT volume). We studied different polymorphisms across the following gene-regulated pathways: oxidation, renin-angiotensin system, cellular, diabetes/obesity and dyslipidemia pathways. Genotyping was performed by TaqMan allelic discrimination assay. A multiplicative genetic risk score (mGRS) was constructed and represents the genetic burden of the different polymorphisms studied. To evaluate the relation between genetics and EAT volume, we compared both groups by: global mGRS, gene cluster/axis mGRS and individual SNPs. Results: Patients with above-median EAT volume were older, had higher body mass index (BMI) and higher prevalence of hypertension, diabetes and dyslipidemia (p<0.05). Patients with higher EAT volumes presented a higher global mean GRS (p<0.001), with the latter remaining an independent predictor for higher EAT volumes (OR 1.3, 95% CI 1.2–1.5), alongside age and BMI. In the analysis by gene clusters, patients with more epicardial fat consistently presented a higher polymorphism burden (translated by a higher mGRS level) across numerous pathways: oxidation, renin-angiotensin system, cellular, diabetes/obesity and dyslipidemia. After adjusting for confounders and other univariate predictors of higher fat volume, the following have emerged as independently related to higher EAT volumes: mGRS comprising the genes of different clusters, age and BMI. Amongst the 33 genes analyzed, only MTHFR677 polymorphisms (a gene with a critical role in regulating plasma homocysteine levels) emerged as significantly related to higher EAT volumes in our population (OR 1.4, 95% CI: 1.100–1.684, p=0.005). Conclusion: Patients with a higher polymorphism burden in genes involved in the oxidation, renin-angiotensin, cellular, diabetes/obesity and dyslipidemia pathways present higher levels of epicardial fat. This potential association seems to be independent from the expected association between epicardial fat and cardiovascular risk factors. To our knowledge, this is the first time such genetic profiling has been done, casting further insight into this complex matter. Funding Acknowledgement: Type of funding source: None